Tackling Unfortunate Legacy: Full Mouth Rehabilitation of Amelogenesis Imperfecta - Nukalamarri; Chary, Om Brahma Prasad; Aswani, Raja Sagi.; Anusha, Rayasam.; Kiranmayi, Thote.; Avinash, Ramavarapu (International Journal of Psychosocial Rehabilitation, 2020)
Amelogenesis imperfecta (AI) is a developmental disturbance which interferes with the normal enamel formation of both primary and permanent dentitions, leading to functional as well as esthetic inadequacies. Diagnosis is based on the family history, pedigree plotting and meticulous clinical observations. So, early recognition followed by appropriate preventive care and oral rehabilitation is essential in the successful management of AI. This clinical report discusses the oral rehabilitation of 14 year old girl diagnosed with hypocalcified autosomal dominant type of amelogenesis imperfecta. A complex set of problems like decreased occlusal vertical height, caries, tooth sensitivity and psychosocial problems related to poor aesthetics were encountered. The treatment protocol followed was mainly focused on aesthetics, functional rehabilitation and also to develop a positive psychological attitude in the patient. This case report depicts the multidisciplinary approach of full mouth rehabilitation in adolescents with AI.